The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s13346-018-0565-x
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin calcium inclusion complexation with polysaccharide arabinogalactan and saponin disodium glycyrrhizate for increasing of solubility and bioavailability

Abstract: The aim of the present investigation was to enhance the solubility and dissolution of atorvastatin calcium (ATV), a poorly water-soluble drug with larch polysaccharide arabinogalactan (AG) and disodium glycyrrhizate (NaGA) as carriers of drug delivery systems for improving its bioavailability. The interactions of ATV with AG or NaGA were investigated by DSC, XRD, SEM, and NMR techniques. The molecular weights of supramolecular systems-inclusion complexes and micelles-which are the hosts for ATV molecules were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In the present study the NMR relaxation technique was applied to prove the formation of NIM inclusion complexes after dissolution of SD in aqueous solutions. Earlier we have shown that the spin-spin nuclear relaxation time T 2 of a drug molecules (carotenoids lutein and zeaxanthin [48], pesticides [49][50][51], anthelmintic drugs albendazole and praziquantel [10,12,44], curcumin [43,52], atorvastatin and simvastatin [42,53], and others [54]) is extremely sensitive to the mobility of the molecules in solution. Formation of inclusion complex with AG, GA or CDs results in a decrease of the diffusion mobility of molecules and leads to decrease in the observed relaxation time of corresponding protons.…”
Section: H-nmr Spectroscopy Of the Aqueous Solutions Of Nim And Its Solid Dispersionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study the NMR relaxation technique was applied to prove the formation of NIM inclusion complexes after dissolution of SD in aqueous solutions. Earlier we have shown that the spin-spin nuclear relaxation time T 2 of a drug molecules (carotenoids lutein and zeaxanthin [48], pesticides [49][50][51], anthelmintic drugs albendazole and praziquantel [10,12,44], curcumin [43,52], atorvastatin and simvastatin [42,53], and others [54]) is extremely sensitive to the mobility of the molecules in solution. Formation of inclusion complex with AG, GA or CDs results in a decrease of the diffusion mobility of molecules and leads to decrease in the observed relaxation time of corresponding protons.…”
Section: H-nmr Spectroscopy Of the Aqueous Solutions Of Nim And Its Solid Dispersionsmentioning
confidence: 99%
“…Glycyrrhizic acid (GA) is a triterpene glycoside extracted from licorice root that demonstrates antiviral, anti-inflammatory, and anticancer properties [37,38]. Due to its amphiphilic properties, GA is capable of forming complexes and micelles [39] with a variety of hydrophobic molecules, substantially increasing their solubility, enhancing the permeability of drugs through cell membranes and their bioavailability [12,[40][41][42][43][44][45][46]. In addition, disodium glycyrrhizin (Na 2 GA) is a salt of GA which can undergo hydrolysis in aqueous solutions and form free GA. Its advantage is that the solution formed has lower viscosity in contrast with GA solutions as far as its potassium salts are concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Solubility values in aqueous media for the amorphous and crystalline forms at 37 °C are 0.11–0.12 mg/mL in water, 0.01 mg/mL in HCl 0.1 N, and 0.72 and 0.70 mg/mL in sodium phosphate 0.05 M pH 7.4, respectively [ 16 ]. Great efforts have been performed to improve ATS oral bioavailability through formulation strategies to increase the solubility and/or dissolution rate of ATS-Ca such as micronization by antisolvent precipitation [ 15 ], microcapsulation [ 17 ], co-grinding techniques [ 18 ], co-amorphous formulations with nicotinamide [ 19 ], dry emulsions [ 13 ], inclusion complexes [ 20 ], and use of drug resinates [ 21 ]. Since ATS is administered mainly as the calcium salt, low solubility in the gastrointestinal (GI) tract should be considered in order to assess its PK characteristics.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…However, the involvement of P-gp in ATS PK has been demonstrated in humans due to the polymorphisms in ABCB1 genotypes, thus suggesting that P-gp affects the enterohepatic recirculation of ATS [ 50 ]. Additionally, ATS is currently considered as a BCS class II (low solubility, high permeability), and many efforts have been made to increase its bioavailability enhancing its solubility [ 14 , 17 , 20 , 71 , 72 ]. For these reasons, solubility and P-gp activity become essential in ATS absorption and disposition.…”
Section: Physiologically Based Pharmacokinetic Models Of Atorvastatinmentioning
confidence: 99%
“…Arabinogalactan is biodegradable, biocompatible and hydrophilic, contains different functional groups such as hydroxyl, carboxylic acid, that make it ideal for conjugation and delivery of carotenoids and drug molecules. There are many examples of increased solubility of hydrophobic drugs in the complexes with AG [72,73,74]. Some recent studies indicate also that AG has good adhesion to membrane surface, and is able to enhance the membrane permeability for both human and plant cell membranes [21,75].…”
Section: Inclusion Complexesmentioning
confidence: 99%